The Modern Sources of Anthropocentrism. Part one - Ganowicz-Bączyk, Anita (Studia Ecologiae et Bioethicae, 2011)
Anthropocentrism seems to be a fundamental notion concerning the man-nature relation. The anthropocentric attitude is largely meant to be the main cause of the ecological crisis. One can distinguish at least several stages of the process, which led to this crisis, namely: stage of Magic and Myth, Ancient Times, Middle Ages, and Modern Times. The aim of this article is to show the process of development of an anthropocentric thought in Modern European culture when the culmination of this process is observed. Among the causes of the modern worldview, one can mention e.g. the modern conception of science (worked out mainly by N. Copernicus, G. Galilei, G. Bruno, F. Bacon, I. Newton, R. Descartes), the technology development, as well as social, political and cultural changes. Both, geocentric and theocentric worldview were rejected. The secularization of European societies shifted to man’s attitude not only towards God but also is creation – nature. People began to treat nature as a challenge and material. God-Creator was replaced by man-designer. A new type of anthropocentrism appeared, which tried to find the answer to the fundamental questions in the human being himself. This resulted in the negation of a strict dependence of mankind on nature and in the tendency to subordinate nature to man. The cognition of nature served then as a means for the sake of mankind only. The man was obliged even to dominate nature which was viewed as a complex of mathematical laws, a value-free mechanism determined by laws of nature. Contemporary view on nature and man was influenced also by philosophical views which on the one hand excluded man from nature (I. Kant) and on the other made attempts to restore man to nature (J. J. Rousseau, F. W. J. Schelling).